Impact of Employer Value Proposition and Social Media Use on the Intention to Apply for a Job in the IT Industry of Vietnam - Pham, Quoc Trung; Vo, Duy Anh (The South East Asian Journal of Management, 2022)
Research Aims: Human resources are critical for success in the digital economy. However, IT human resources are predicted to be scarce and attracting IT talent is difficult for many enterprises. Currently, employer branding and social media advertising are possible solutions to these problems. This research aims to evaluate the influence of EVP and social media use on the intention to apply for an IT job. Design/Methodology/Approach: The quantitative research method is used to verify the research model. The sample includes 240 valid respondents from HCMC, Vietnam. The research model includes six independent variables (5 values of EVP and social media use) affecting the intention to apply for a job through organisational reputation. Some analysis methods used include Descriptive Statistics, Cronbach’s Alpha, EFA, Multiple Regression, and Bootstrap Analysis. Research Findings: The results show that 4/5 of the values (except management value) and social media use have positive impacts on reputation and, in turn, on the intention to apply for a job. Theoretical Contribution/Originality: This research clarifies the role of employer branding and social media use in attracting talent to the Vietnamese IT industry. The mediating role of organisational reputation is also confirmed using the bootstrapping method. Managerial Implication in the South East Asian Context: Based on the results, some recommendations have been made to improve the attractiveness of the IT industry in Vietnam and the ASEAN context. Research Limitations & Implications: Limitations of the study include the small sample size and lack of other aspects of employer branding. So, increasing the sample size and adding some other factors could be implications for future research directions.